A sociodemographic evaluation of cases applying to a child and adolescent dependency centre during a period of two years attending ege university faculty of science - Yüncü, Zeki; Aydın, Cahide; Coşkunol, Hakan; Altıntoprak, Ender; Bayram, Ayşe Türkan (Journal of Dependence, 2006)
Objective: EGEBAM is a ne^^ addiction centre that had been in operation since September 2003. We have planned this study in order to assess some clinical characteristics of cases that came to our centre. Method: The outpatient records belonging to cases that came to our service bet^^een September 2003 – September 2005 have been revie^^ed. We have reached a total of 323 cases. The data obtained from the outpatient records ^^ere entered in an information form, ^^hich has been developed by us. Results: 323 cases had applied to EGEBAM. 88.5 %of these is 323 cases is of male gender and 11.5 %is female. The mean is 16.2. 52.3 %of the cases have social security ^^hereas 47.7%do not have any. It has been found that 94.4%of these cases smoke and 5.6%do not. 93.8 %of all cases take or smoke substance other than cigarette ^^hereas 6.2 %do not. The most common substance used is cigarette (94.4%). This is follo^^ed by marijuana (75.2 %), inhalant (53.8 %), ecstasy (43.6 %), alcohol (43.2 %), benzodiazepines (31.4 %), cocaine (2.6 %), other tablets (1.7 %), opioids(0.3 %). When smoking is excluded, it has been observed that 86.9 %of the cases are the multiple substance users. The onset age of cases ^^ho participated in this study ^^as 13.7 ±2.16. The age, ^^hen they came for the treatment is 16± 16±1.65. There is 29 ±29±23.98 month bet^^een the onset and treatment on average. Conclusion: In terms of some clinical parameters (most preferred substances, onset age, outpatients rate), child and adolescent substance users differ from adult substance users.